(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: The first description of Jalaukavacharana (leech therapy) was found in the text of Sushruta Samhita in 800 B.C. Recently, many researches proved that leech saliva have variety of bioactive compounds involving anti-thrombin (hirudin, bufrudin), anti-platelet (calin), factor Xa inhibitors, antibacterial and others property. Aim: Main aim of present article is to explore about procedures of leech therapy and research works done over few decades on application of leech therapy in different medico-surgical diseases. Methodology: The procedure of leech therapy is documented from authors own observations and Information of its application in different diseases was gathered from various published work of last ten years. Result:-Many clinical researches show that leech therapy is very effective in various medico-surgical diseases. Total eight publications were included in the final selection after systematic analysis. Conclusion: -Leech therapy or Jalaukavacharan is an ancient Ayurvedic bloodletting technique which having the great potential to manage many inflammatory, ischemic and infectious diseases. Leech’s saliva contains many biologically and pharmacologically active compounds which exert effects anti-coagulant, profibrinolytic, anti-platelet, anti-inflammatory and anti-edema in the host’s body. Arthritis, venous congestion, vascular diseases, abscess, ischemic heart disease etc. can be successfully manage by leech therapy/.